Identification of a stripe rust resistance gene in Chinese wheat line Shaannong69 using bulked-segregant sequencing - Yan Dong; Yachao Dong; Ling Wu; Jianhui Wu; Yukun Cheng; Dengan Xu; Yuying Wu; Fengju Wang; Bin Bai; Jingchun Wu; Yan Ren; Yuanfeng Hao; et al. (Springer, 2024)
Stripe rust, caused by Puccinia striiformis f. sp. tritici (Pst), is a devastating fungal disease, leading to huge yield losses in wheat production. Identification of resistance genes and closely linked molecular markers can greatly facilitate breeding resistant wheat cultivars. Shaannong69 conferred high resistance to stripe rust both at the seedling and adult-plant stages. The Pst race CYR31 was used to infect Shaannong69, Huixianhong, F1 and F2 plants and F2:3 lines at the seedling stage in the greenhouse. Genetic analysis identified a single dominant gene, designated as YrSN69, conferring resistance to Pst race CYR31 in Shaannong69. Seventy-four of 176 SNPs with the absolute value of triangle SNP-index more than 0.85 were identified in 753.33-766.18 Mb on chromosome 2BL based on bulked segregant RNA sequencing. Fifteen kompetitive allele-specific PCR markers were developed to genotype susceptible F2 plants derived from the Shaannong69/Huixianhong cross. YrSN69 was mapped on chromosome arm 2BL in a 2.0 cM genetic interval, with genetic distances of 0.2 cM and 1.8 cM to markers 2BC17 and 2BA20, respectively, corresponding to a 3.16 Mb physical region based on the IWGSC RefSeq v1.1 with 44 high-confidence annotated genes. The YrSN69 is likely to be a new allele of Yr72 in comparison with known Yr genes on chromosome 2BL. These results provide a solid foundation for map-based cloning of YrSN69 and marker-assisted selection for pyramiding stripe rust resistance genes.